Pengaruh Gender pada Pengembangan Diri Mahasiswa dalam Konteks Perguruan Tinggi Menggunakan Statistika Nonparametrik - Yang, Valerie Vincent; Safitri, Rahmah Nadia; Khairunnisa, Hanifah; Faidah, Defi Yusti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Self-development is an important aspect that is the goal of a student to express abilities, interests, and talents through activities and activities inside and outside an educational institution. The study aims to determine the relationship between differences in answers based on gender with factors influencing student self-development with a nonparametric statistical method approach. Followed by a nonparametric statistical method, namely the Chi-Square test, with α = 5%. The results showed that there was no difference between male and female students in the influence factors of lecturer teaching methods, friendship environments, organizations/committees, and courses on student self-development